High-conductivity foam and preparation method thereof
By forming nanoseeds in the conductive foam and growing silver nanowires to fill the internal holes, the problems of insufficient conductivity and mechanical properties of the existing conductive foam are solved, and the effects of high conductivity and high rebound are achieved.
Patent Information
- Application Number
- CN202411178388.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
When filling conductive materials, existing conductive foams can only be performed on the surface and cannot effectively fill internal holes, resulting in insufficient conductivity and mechanical properties and inability to meet the application fields of high conductivity requirements.
Clean the foam by soaking it in a silane coupling agent solution, then adding silver salt to the solution containing chloride or bromide ions to form nanoseeds, and then heating the silver nanowires in the silver salt solution to fill the holes inside the foam , and a conductive network is formed during the curing process.
Achieve uniform filling of conductive materials inside the foam, significantly improve the conductivity and mechanical rebound properties, avoid the dispersion of nanomaterials, improve the adhesion and durability of nano silver wires, so that conductive foam can be used in high-quality Areas of electrical conductivity and high rebound.
Smart Images

Figure CN119207862A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a highly conductive foam and a preparation method thereof. Background Art
[0002] Conventional conductive foams on the market only conduct electricity on the surface of the foam, and the pores inside the foam are not filled, resulting in very general conductivity and rebound performance. They are generally only used for electromagnetic shielding and cannot be used in fields with high conductivity requirements. At present, conductive foams are generally prepared by the following three methods: one is to electroplating conductive metals such as silver, copper, and nickel on the surface of the foam, the second is to directly attach conductive glue to the surface of the foam, and the third is to dope conductive materials, but the conductive materials are all inside the foam and cannot form a linking effect. High conductivity, maintaining the mechanical properties of the foam, and uniform filling inside the foam are effects that foams cannot achieve at this stage, because the pores of the conventionally used foams are empty, and the rebound and resistance can only remain at a very weak level, and the adhesion will also be poor.
[0003] Based on the defects in the current preparation of conductive foam, it is necessary to improve it. Summary of the invention
[0004] In view of this, the present invention proposes a highly conductive foam and a preparation method thereof to solve the technical problems existing in the prior art.
[0005] In a first aspect, the present invention provides a method for preparing a highly conductive foam, comprising the following steps:
[0006] Soaking the foam in a silane coupling agent solution, and then washing the foam;
[0007] The washed foam is immersed in a solution containing chloride ions and / or bromide ions, and then a silver salt is added and stirred to form nano seeds on the surface and inside of the foam;
[0008] placing the foam with the nano seeds formed thereon in a first silver salt solution and heating it to form silver nanowires on the surface and inside of the foam;
[0009] washing the foam formed with the silver nanowires;
[0010] Curing the washed foam at 40-180°C;
[0011] Wherein, the first silver salt solution comprises silver salt, ethylene glycol and polyvinyl pyrrolidone.
[0012] Preferably, the foam formed with the nano seeds is placed in the first silver salt solution, heated and stirred at 100-190° C., and the second silver salt solution is added dropwise to the first silver salt solution again; the reaction is stirred for 30-60 minutes;
[0013] Wherein, the second silver salt solution includes silver salt, ethylene glycol and polyvinyl pyrrolidone.
[0014] Preferably, the mass fraction of silver salt in the first silver salt solution is 0.5-10%, and the mass fraction of polyvinyl pyrrolidone is 0.5-10%;
[0015] And / or, the mass fraction of silver salt in the second silver salt solution is 1-15%, and the mass fraction of polyvinyl pyrrolidone is 0.05-2.5%;
[0016] and / or, the mass of the second silver salt solution is 20 to 150% of the mass of the first silver salt solution;
[0017] And / or, the silver salt in the first silver salt solution and the silver salt in the second silver salt solution include at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide and silver acetate.
[0018] Preferably, the solution containing chloride ions and / or bromide ions comprises a chloride salt and / or a bromide salt and a first solvent;
[0019] The chloride salt includes at least one of sodium chloride, potassium chloride, ferric chloride, ferrous chloride, cobalt chloride, nickel chloride, cupric chloride and zinc chloride;
[0020] And / or, the bromide salt includes at least one of sodium bromide, potassium bromide, ferric bromide, ferrous bromide, cobalt bromide, nickel bromide, copper bromide and zinc bromide;
[0021] and / or, the first solvent comprises at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol;
[0022] And / or, the mass concentration of chloride salt or bromide salt in the solution containing chloride ions and / or bromide ions is 0.1-5%.
[0023] Preferably, the silane coupling agent solution comprises a silane coupling agent and a second solvent;
[0024] The silane coupling agent includes at least one of KH-171, KH-172, KH-350, KH-360, KH-370, KH-550, KH-560, KH-570, KH-580, and KH-590;
[0025] and / or, the second solvent comprises water and / or alcohol, and the alcohol comprises at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol;
[0026] And / or, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.01-5%.
[0027] Preferably, the foam formed with the silver nanowires is washed with a third solvent;
[0028] The third solvent comprises at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, ethyl acetate, butyl acetate, acetone, butanone, and methyl ethyl ether;
[0029] And / or, the washing time is 5 to 60 minutes.
[0030] Preferably, the foam is immersed in a silane coupling agent solution and stirred at 100-1000 rpm for 10-120 min, and then washed with an alcohol solvent; the alcohol solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.
[0031] Preferably, the washed foam is immersed in a solution containing chloride ions and / or bromide ions, stirred for 10 to 30 minutes, then silver salt is added, and stirred again for 10 to 30 minutes to form nano seeds on the surface and inside of the foam;
[0032] The silver salt is added in the form of a third silver salt solution, the third silver salt solution comprises a silver salt and a fourth solvent, and the silver salt comprises at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide, and silver acetate;
[0033] The fourth solvent includes at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol;
[0034] The mass concentration of silver salt in the third silver salt solution is 0.1-5%.
[0035] Preferably, the second solvent comprises water and alcohol, and the volume ratio of water to alcohol is 1:(1-3);
[0036] And / or, the foam is polyurethane foam.
[0037] In a second aspect, the present invention further provides a highly conductive foam, which is prepared by the preparation method.
[0038] The preparation method of the highly conductive foam of the present invention has the following beneficial effects compared with the prior art:
[0039] The preparation method of the highly conductive foam of the present invention directly grows highly conductive nano silver wires in situ on the surface and inside of the foam, and fills the internal pores of the foam with the grown highly dispersed nano silver wires, so that not only the conductive effect is achieved on the surface of the foam pores, but also conductive filling is performed in the foam pores, thereby greatly improving the overall conductive performance of the foam, while improving the mechanical rebound performance of the foam, and avoiding the dispersion problem caused by excessive accumulation of nano materials. At the same time, the directly grown nano silver wires have better adhesion and are less likely to fall off, so as to improve durability. The conductive foam prepared by this method can be used in high-conductivity and high-resilience application fields, rather than just in the electromagnetic shielding field with lower use requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 This is a scanning electron microscope image of the highly conductive foam prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0044] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0045] The present invention provides a method for preparing a highly conductive foam, comprising the following steps:
[0046] S1, soaking the foam in a silane coupling agent solution, and then washing the foam;
[0047] S2, soaking the washed foam in a solution containing chloride ions and / or bromide ions, then adding silver salt and stirring to form nano seeds on the surface and inside of the foam;
[0048] S3, placing the foam with the nano seeds in a first silver salt solution, and heating it to form silver nanowires on the surface and inside of the foam;
[0049] S4, washing the foam formed with the silver nanowires;
[0050] S5, curing the washed foam at 40-180°C;
[0051] Wherein, the first silver salt solution comprises silver salt, ethylene glycol and polyvinyl pyrrolidone.
[0052] The method for preparing the highly conductive foam of the present invention comprises the following steps:
[0053] S1. Soak the foam in a silane coupling agent solution and then wash the foam. Specifically, the silane coupling agent solution is used to clean the surface and interior of the foam. The main purpose is to remove organic residues on the surface and interior of the foam and add more hydrophilic functional groups, such as hydroxyl, amino, carboxyl, etc.
[0054] S2, soaking the foam in a solution containing chloride ions and / or bromide ions, then adding silver salt and stirring to form nano seeds on the surface and inside of the foam; specifically, the growth of the nano seeds on the surface of the foam and the surface of the internal holes is mainly to allow the nano seeds to grow on the surface or inside of the foam, thereby facilitating the growth of the nano silver wires from the seeds, and the presence of the seeds can greatly improve the adhesion of the nano silver wires inside the foam, providing a chemical bond effect compared to the conventional physical adsorption method;
[0055] S3, placing the foam with the nano seeds in the first silver salt solution, and heating it to form silver nanowires on the surface and inside of the foam; the growth of the nano silver wires is mainly to allow the nano silver wires to grow on the surface and internal pores of the foam relying on the nano seeds, and the nano silver wires grown by the nano seeds will have greatly improved adhesion and conductivity;
[0056] S4, washing the foam formed with silver nanowires; The foam formed with silver nanowires is washed to remove impurities generated during the growth of the nano silver wires and residual ethylene glycol, polyvinyl pyrrolidone and incompletely reacted silver salts (such as silver nitrate) during the production process;
[0057] S5. Curing the washed foam at 40-180°C. The main purpose of curing the washed foam at 40-180°C is to allow the nano silver wires to form a molten network structure inside the foam pores to form a better conductive effect, thereby further improving the conductive properties of the conductive foam, and also allowing some of the residual cleaning liquid to evaporate well. Specifically, the washed foam is placed in an oven and taken out after a certain curing time; the curing temperature is generally set at 40-180°C. If the temperature is too low, the drying efficiency is too low, and the residual solvent from the cleaning may not evaporate. If the temperature is too high, it will affect the stability of the foam, and the foam may collapse, thereby affecting the rebound performance.
[0058] The present invention directly grows highly conductive nano silver wires in situ on the surface and inside of the foam, and fills the internal pores of the foam with the grown highly dispersed nano silver wires, thereby achieving a conductive effect not only on the surface of the foam pores, but also conducting filling in the foam pores, thereby greatly improving the overall conductive performance of the foam, while improving the mechanical rebound performance of the foam, and avoiding the dispersion problem caused by excessive accumulation of nano materials. At the same time, the directly grown nano silver wires have better adhesion and are less likely to fall off, thereby improving durability; the conductive foam prepared by the method can be used in high-conductivity and high-resilience application fields, rather than just in the electromagnetic shielding field with lower use requirements; the present invention uses the conductive foam treated by the above S1 to S5, and the nano silver wires are grown inside the foam, and the nano silver wires are grown on the surface of the foam and the pores of the foam, so that the foam forms a conductive continuous network under the action of the nano silver wires, and when the pores are filled, better rebound performance can be achieved. The present invention can greatly improve the conductivity and resilience of the conductive foam by in-situ growing of nano silver wires inside the foam, so that the conductive foam can be used not only in the field of electromagnetic shielding, but also in the field of conduction, especially in the field where compression rebound and conduction are required at the same time.
[0059] In some embodiments, the foam formed with nano seeds is placed in a first silver salt solution, heated and stirred at 100-190° C., and a second silver salt solution is added dropwise to the first silver salt solution again; the reaction is stirred for 30-60 minutes;
[0060] Wherein, the second silver salt solution includes silver salt, ethylene glycol and polyvinyl pyrrolidone.
[0061] In some embodiments, the mass fraction of silver salt in the first silver salt solution is 0.5-10%, and the mass fraction of polyvinyl pyrrolidone is 0.5-10%;
[0062] In some embodiments, the mass fraction of the silver salt in the second silver salt solution is 1-15%, and the mass fraction of the polyvinyl pyrrolidone is 0.05-2.5%.
[0063] In some embodiments, the mass of the second silver salt solution is 20-150% of the mass of the first silver salt solution.
[0064] In some embodiments, the silver salt in the first silver salt solution and the silver salt in the second silver salt solution include at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide, and silver acetate.
[0065] In the above embodiment, the foam formed with nano seeds is placed in a first silver salt solution, heated and stirred at 100-190° C., and the second silver salt solution is added to the first silver salt solution again during the stirring process to allow the nano silver wires to grow longer. After the foam is completely and evenly blackened, it indicates that the growth is completed; the mass fraction of the silver salt in the first silver salt solution is 0.5-10%, the mass fraction of polyvinyl pyrrolidone is 0.5-10%, and the rest is ethylene glycol, which is used as a solvent and a reducing agent; the heating temperature needs to reach the temperature point at which ethylene glycol reacts with silver salt (such as silver nitrate), which is generally 100-190° C. If the temperature is too low, ethylene glycol will not react with silver salt (such as silver nitrate) and growth cannot be achieved; if the temperature is too high, ethylene glycol will boil, affecting The second silver salt solution added also includes silver salt, ethylene glycol and polyvinyl pyrrolidone, and its function is to further grow the nano silver wires. If the silver source is not supplemented, the overall nano silver wires cannot grow to the target length. Therefore, the amount of the second silver salt solution added needs to be within a reasonable range, generally 20-150% of the mass of the first silver salt solution. If too little is added, the nano silver wires grow too short and are not long enough. If too much is added, the nano silver wires grow too long and are prone to block the holes on the surface, thereby forming an uneven growth of the nano silver wires inside and outside. The mass content of silver salt in the second silver salt solution is higher, reaching 1-15%, the mass fraction of polyvinyl pyrrolidone is 0.05-2.5%, and the rest is ethylene glycol.
[0066] In some embodiments, the solution containing chloride ions and / or bromide ions comprises a chloride salt and / or a bromide salt and a first solvent;
[0067] In some embodiments, the chloride salt includes at least one of sodium chloride, potassium chloride, ferric chloride, ferrous chloride, cobalt chloride, nickel chloride, cupric chloride, and zinc chloride.
[0068] In some embodiments, the bromide salt includes at least one of sodium bromide, potassium bromide, ferric bromide, ferrous bromide, cobalt bromide, nickel bromide, copper bromide, and zinc bromide.
[0069] In some embodiments, the first solvent includes at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol.
[0070] In some embodiments, the mass concentration of chloride salt or bromide salt in the solution containing chloride ions and / or bromide ions is 0.1-5%.
[0071] In some embodiments, the washed foam is immersed in a solution containing chloride ions and / or bromide ions, stirred for 10 to 30 minutes, then a silver salt is added, and stirred again for 10 to 30 minutes to form nano seeds on the surface and inside of the foam;
[0072] The silver salt is added in the form of a third silver salt solution, the third silver salt solution comprises a silver salt and a fourth solvent, and the silver salt comprises at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide, and silver acetate;
[0073] The fourth solvent includes at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol;
[0074] The mass concentration of silver salt in the third silver salt solution is 0.1-5%.
[0075] In the above embodiment, the foam is soaked in a solution containing chloride ions and / or bromide ions, and after stirring for a period of time, the third silver salt solution is added to generate silver chloride / silver bromide seeds, and after stirring for a period of time, the seeds are left to dry. The chloride / bromide ions used can be one or more of the following, including: sodium salts, potassium salts, iron salts, ferrous salts, cobalt salts, nickel salts, copper salts, zinc salts, etc. of chloride / bromide. The mass concentration of chloride or bromide in the solution is 0.1-5%. Too little may result in insufficient adsorption of seeds on the surface, and too much may result in too many seeds in the solution, which will affect subsequent growth. The first solvent can be selected from conventional solvents that can dissolve these salts, including: water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, glycerol, etc. The silver salt in the third silver salt solution is generally dissolved in the same solvent as the first solvent, and the mass concentration of the silver salt in the third silver salt solution is 0.1-5%. Stir until the solution changes color, usually red, brown, or orange, indicating that the surface seeds have been formed. Stir for another 10 to 30 minutes to allow them to further react on the foam surface.
[0076] In some embodiments, the silane coupling agent solution includes a silane coupling agent, a second solvent;
[0077] The silane coupling agent includes at least one of KH-171, KH-172, KH-350, KH-360, KH-370, KH-550, KH-560, KH-570, KH-580, and KH-590.
[0078] In some embodiments, the second solvent includes water and / or alcohol, and the alcohol includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.
[0079] In some embodiments, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.01-5%.
[0080] In some embodiments, the second solvent includes water and alcohol, and the volume ratio of water to alcohol is 1:(1-3).
[0081] In some embodiments, the foam is immersed in a silane coupling agent solution and stirred at 100-1000 rpm for 10-120 min, and then washed with an alcohol solvent; the alcohol solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.
[0082] In the above embodiment, the silane coupling agent solution is used to clean the surface and the inside of the foam, the main purpose of which is to remove organic residues on the surface and the inside of the foam, and to add more hydrophilic functional groups, such as hydroxyl, amino, carboxyl, etc.; specifically, the foam is immersed in the silane coupling agent solution and stirred and cleaned for a certain period of time, and then the silane coupling agent that is not cross-linked on the surface is washed away with an alcohol solvent that does not contain a silane coupling agent, and finally allowed to stand and dry; wherein the silane coupling agent used is generally one or more of the conventionally used silane coupling agents, including: KH-171, KH-172, KH-350, KH-360, KH-370, KH-550, KH-560, KH-570, KH-580, KH-590, etc.; the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.01-5%. If too much is added, there will not be enough surface for silane coupling agent to modify. Excess will produce silicon dioxide attached to the foam surface and affect the resistance. If too little is added, it will not be enough to completely modify the foam surface. The second solvent includes water and / or alcohol. Alcohol is generally selected from conventional solvents that are miscible with water. One or more of the following methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, etc. can be selected. The role of adding water is to add some hydroxyl groups to the foam surface, so that there are more growth sites later. The second solvent includes water and alcohol. The volume ratio of water to alcohol is 1: (1-3). If the water content is too low, the number of hydroxyl groups is insufficient, which will affect the growth of silver wires later. If the water content is too high, it is not easy to clean the grease on the foam surface, resulting in insufficient growth sites, thereby affecting the growth of silver wires. Soak the foam in the silane coupling agent solution and stir at 100-1000rpm for 10-120min. Select the optimal stirring speed according to different stirring methods, and clean the foam surface until the hydrophilicity meets the requirements.
[0083] In some embodiments, the foam formed with silver nanowires is washed with a third solvent;
[0084] The third solvent includes at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, ethyl acetate, butyl acetate, acetone, butanone, and methyl ethyl ether;
[0085] The washing time is 5 to 60 minutes.
[0086] In the above embodiment, the third solvent is used to wash the foam formed with silver nanowires, the main purpose of which is to remove impurities generated during the growth of nanosilver wires and residual ethylene glycol, polyvinyl pyrrolidone and incompletely reacted silver salts (such as silver nitrate) during the production process; specifically, the foam formed with silver nanowires is placed in the third solvent, stirred, and the excess impurities and residual substances are washed. The cleaning solution is generally a relatively volatile solvent with better solubility in impurities. The third solvent is generally a mixture of one or more of the following: methanol, ethanol, isopropanol, n-butanol, isobutanol, ethyl acetate, butyl acetate, acetone, butanone, methyl ethyl ether and other conventional solvents; the cleaning time is generally 5 to 60 minutes to remove the impurities inside the foam. If the time is too short, it is not easy to clean it. If the time is too long, it is easy to wash the grown nanosilver wires together.
[0087] In some embodiments, the foam is polyurethane foam.
[0088] Specifically, the foam of the present invention is generally selected from conventional polyurethane foam, and the average pore diameter inside the foam is 20 to 100 μm, so that it is suitable for the growth of nano silver wires; there is no requirement for the size of the foam, as long as it can meet the size of the container and can still stretch inside the container after absorbing water and swelling instead of existing in the form of shrinkage and agglomeration. The foam of the present invention takes a square polyurethane foam of 50mm×50mm×2.5mm (i.e., a length of 50mm, a width of 50mm, and a height of 2.5mm) as an example, and the expansion coefficient after absorbing water is 1.2 to 1.5 times.
[0089] Based on the same inventive concept, the present invention also provides a highly conductive foam, which is prepared by the above-mentioned preparation method.
[0090] The highly conductive foam and its preparation method of the present application are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0091] Example 1
[0092] The present invention provides a method for preparing a highly conductive foam, comprising the following steps:
[0093] S1. Soak a 50mm×50mm×2.5mm (i.e., 50mm in length, 50mm in width, and 2.5mm in height) polyurethane foam in a silane coupling agent solution and stir at 500rpm for 30min; then wash the polyurethane foam with an alcohol solvent; wherein the silane coupling agent solution comprises a silane coupling agent and a second solvent, the silane coupling agent is KH-360 (i.e., n-octyltriethoxysilane), the second solvent comprises water, ethanol, and n-butanol in a volume ratio of 1:1:1; the alcohol solvent comprises ethanol and n-butanol in a volume ratio of 1:1; the mass concentration of KH-360 in the silane coupling agent solution is 1%;
[0094] S2, soaking the washed polyurethane foam in S1 in a solution containing chloride ions and bromide ions, stirring for 20 minutes, then adding the third silver salt solution, and stirring again for 30 minutes to form nano seeds on the surface and inside of the foam;
[0095] The solution containing chloride ions and bromide ions includes ferric chloride, sodium bromide and a first solvent, and the first solvent includes water and ethanol in a volume ratio of 1:1; the mass concentration of ferric chloride in the solution containing chloride ions and bromide ions is 0.4%, and the mass concentration of sodium bromide is 0.6%;
[0096] The third silver salt solution includes a silver salt and a fourth solvent, wherein the silver salt is silver nitrate, the fourth solvent includes water and ethanol in a volume ratio of 1:1, and the mass concentration of silver nitrate in the third silver salt solution is 1%;
[0097] S3, placing the polyurethane foam with nano seeds formed in S2 in the first silver salt solution, heating and stirring at 140° C., and simultaneously adding the second silver salt solution dropwise to the first silver salt solution again, stirring and reacting for 60 minutes, so as to form silver nanowires on the surface and inside of the foam;
[0098] Wherein, the first silver salt solution and the second silver salt solution both include silver salt, ethylene glycol, and polyvinyl pyrrolidone; the silver salt is silver nitrate;
[0099] The mass concentration of silver nitrate in the first silver salt solution is 1%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0100] The mass concentration of silver nitrate in the second silver salt solution is 2%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0101] The mass of the second silver salt solution is 50% of the mass of the first silver salt solution;
[0102] S4, placing the polyurethane foam with silver nanowires formed in S3 in a third solvent, stirring for 10 minutes, and washing away excess impurities and residual substances; the third solvent is ethyl acetate;
[0103] S5. Place the polyurethane foam washed in S4 in an oven at 120° C. and cure for 30 minutes to obtain a highly conductive foam.
[0104] Example 2
[0105] The method for preparing the highly conductive foam provided in this embodiment is the same as that in Embodiment 1, except that step S1 is specifically as follows:
[0106] S1. Soak a 50mm×50mm×2.5mm (i.e., 50mm in length, 50mm in width, and 2.5mm in height) polyurethane foam in a silane coupling agent solution and stir at 300rpm for 20min; then wash the polyurethane foam with an alcohol solvent; wherein the silane coupling agent solution comprises a silane coupling agent and a second solvent, the silane coupling agent is KH-560 (i.e., γ-glycidyloxypropyltrimethoxysilane), and the second solvent comprises water and isopropanol in a volume ratio of 2:1; the mass concentration of KH-560 in the silane coupling agent solution is 0.1%;
[0107] Steps S2 to S5 are the same as those in Example 1.
[0108] Example 3
[0109] The method for preparing highly conductive foam provided in this embodiment is the same as that in Embodiment 1, except that in step S2, the solution containing chloride ions includes sodium chloride, copper chloride and a first solvent, the first solvent includes ethylene glycol and ethanol in a volume ratio of 3:1; the mass concentration of sodium chloride in the solution containing chloride ions is 0.2%, and the mass concentration of copper chloride is 0.2%;
[0110] The third silver salt solution includes a silver salt and a fourth solvent, wherein the silver salt is silver nitrate, the fourth solvent is ethylene glycol, and the mass concentration of silver nitrate in the third silver salt solution is 0.6%;
[0111] Steps S1 and S3 to S5 are the same as those in Example 1.
[0112] Example 4
[0113] The method for preparing highly conductive foam provided in this embodiment is the same as that in Embodiment 1, except that in step S3, the mass concentration of silver nitrate in the first silver salt solution is 2%, and the mass concentration of polyvinyl pyrrolidone is 5%; the mass concentration of silver nitrate in the second silver salt solution is 5%, and the mass concentration of polyvinyl pyrrolidone is 5%;
[0114] The mass of the second silver salt solution is 100% of the mass of the first silver salt solution;
[0115] Steps S1-S2 and S4-S5 are the same as those in Example 1.
[0116] Example 5
[0117] The method for preparing highly conductive foam provided in this embodiment is the same as that in Embodiment 1, except that the third solvent used in step S4 comprises ethanol and acetone in a volume ratio of 1:1;
[0118] In step S5, the polyurethane foam is placed in an oven at 90° C. and cured for 60 minutes;
[0119] Steps S1 to S3 are the same as those in Example 1.
[0120] Comparative Example 1
[0121] The conductive foam provided in this comparative example is commercially available conventional nickel-plated conductive foam.
[0122] Comparative Example 2
[0123] The preparation method of the conductive foam provided in this comparative example is the same as that in Example 1, except that step S2 is omitted, and specifically comprises:
[0124] S1. Soak a 50mm×50mm×2.5mm (i.e., 50mm in length, 50mm in width, and 2.5mm in height) polyurethane foam in a silane coupling agent solution and stir at 500rpm for 30min; then wash the polyurethane foam with an alcohol solvent; wherein the silane coupling agent solution comprises a silane coupling agent and a second solvent, the silane coupling agent is KH-360 (i.e., n-octyltriethoxysilane), the second solvent comprises water, ethanol, and n-butanol in a volume ratio of 1:1:1; the alcohol solvent comprises ethanol and n-butanol in a volume ratio of 1:1; the mass concentration of KH-360 in the silane coupling agent solution is 1%;
[0125] S2, placing the washed polyurethane foam in S1 in the first silver salt solution, heating and stirring at 140° C., and simultaneously adding the second silver salt solution dropwise to the first silver salt solution again, stirring and reacting for 60 minutes, so as to form silver nanowires on the surface and inside of the foam;
[0126] Wherein, the first silver salt solution and the second silver salt solution both include silver salt, ethylene glycol, and polyvinyl pyrrolidone; the silver salt is silver nitrate;
[0127] The mass concentration of silver nitrate in the first silver salt solution is 1%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0128] The mass concentration of silver nitrate in the second silver salt solution is 2%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0129] The mass of the second silver salt solution is 50% of the mass of the first silver salt solution;
[0130] S3, placing the polyurethane foam with silver nanowires formed in S2 in a third solvent, stirring for 10 minutes, and washing away excess impurities and residual substances; the third solvent is ethyl acetate;
[0131] S4. Place the washed polyurethane foam in S4 in an oven at 120° C. and cure for 30 minutes to obtain a conductive foam.
[0132] Comparative Example 3
[0133] The preparation method of the conductive foam provided in this comparative example is the same as that in Example 1, except that step S3 is omitted, and specifically comprises:
[0134] The present invention provides a method for preparing a highly conductive foam, comprising the following steps:
[0135] S1. Soak a 50mm×50mm×2.5mm (i.e., 50mm in length, 50mm in width, and 2.5mm in height) polyurethane foam in a silane coupling agent solution and stir at 500rpm for 30min; then wash the polyurethane foam with an alcohol solvent; wherein the silane coupling agent solution comprises a silane coupling agent and a second solvent, the silane coupling agent is KH-360 (i.e., n-octyltriethoxysilane), the second solvent comprises water, ethanol, and n-butanol in a volume ratio of 1:1:1; the alcohol solvent comprises ethanol and n-butanol in a volume ratio of 1:1; the mass concentration of KH-360 in the silane coupling agent solution is 1%;
[0136] S2, soaking the washed polyurethane foam in S1 in a solution containing chloride ions and bromide ions, stirring for 20 minutes, then adding the third silver salt solution, and stirring again for 30 minutes to form nano seeds on the surface and inside of the foam;
[0137] The solution containing chloride ions and bromide ions includes ferric chloride, sodium bromide and a first solvent, and the first solvent includes water and ethanol in a volume ratio of 1:1; the mass concentration of ferric chloride in the solution containing chloride ions and bromide ions is 0.4%, and the mass concentration of sodium bromide is 0.6%;
[0138] The third silver salt solution includes a silver salt and a fourth solvent, wherein the silver salt is silver nitrate, the fourth solvent includes water and ethanol in a volume ratio of 1:1, and the mass concentration of silver nitrate in the third silver salt solution is 1%;
[0139] S3, placing the polyurethane foam in S2 in a third solvent, stirring for 10 minutes, and washing away excess impurities and residual substances; the third solvent is ethyl acetate;
[0140] S4. Place the washed polyurethane foam in S3 in an oven at 120° C. and cure for 30 minutes to obtain a conductive foam.
[0141] Comparative Example 4
[0142] The preparation method of the conductive foam provided in this comparative example is the same as that in Example 1, except that steps S4 to S5 are omitted, and specifically comprises:
[0143] S1. Soak a 50mm×50mm×2.5mm (i.e., 50mm in length, 50mm in width, and 2.5mm in height) polyurethane foam in a silane coupling agent solution and stir at 500rpm for 30min; then wash the polyurethane foam with an alcohol solvent; wherein the silane coupling agent solution comprises a silane coupling agent and a second solvent, the silane coupling agent is KH-360 (i.e., n-octyltriethoxysilane), the second solvent comprises water, ethanol, and n-butanol in a volume ratio of 1:1:1; the alcohol solvent comprises ethanol and n-butanol in a volume ratio of 1:1; the mass concentration of KH-360 in the silane coupling agent solution is 1%;
[0144] S2, soaking the washed polyurethane foam in S1 in a solution containing chloride ions and bromide ions, stirring for 20 minutes, then adding the third silver salt solution, and stirring again for 30 minutes to form nano seeds on the surface and inside of the foam;
[0145] The solution containing chloride ions and bromide ions includes ferric chloride, sodium bromide and a first solvent, and the first solvent includes water and ethanol in a volume ratio of 1:1; the mass concentration of ferric chloride in the solution containing chloride ions and bromide ions is 0.4%, and the mass concentration of sodium bromide is 0.6%;
[0146] The third silver salt solution includes a silver salt and a fourth solvent, wherein the silver salt is silver nitrate, the fourth solvent includes water and ethanol in a volume ratio of 1:1, and the mass concentration of silver nitrate in the third silver salt solution is 1%;
[0147] S3, placing the polyurethane foam with nano seeds formed in S2 in the first silver salt solution, heating and stirring at 140° C., and simultaneously adding the second silver salt solution dropwise to the first silver salt solution again, stirring and reacting for 60 minutes, so as to form silver nanowires on the surface and inside of the foam, thereby obtaining a conductive foam;
[0148] Wherein, the first silver salt solution and the second silver salt solution both include silver salt, ethylene glycol, and polyvinyl pyrrolidone; the silver salt is silver nitrate;
[0149] The mass concentration of silver nitrate in the first silver salt solution is 1%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0150] The mass concentration of silver nitrate in the second silver salt solution is 2%, and the mass concentration of polyvinyl pyrrolidone is 1%;
[0151] The mass of the second silver salt solution is 50% of the mass of the first silver salt solution.
[0152] Performance Testing
[0153] The scanning electron microscope image of the highly conductive foam prepared in Example 1 is as follows: Figure 1 shown.
[0154] from Figure 1 It can be seen that the surface of the highly conductive foam prepared in Example 1 and the internal pores of the foam are full of nano silver wires, so that the foam forms a conductive continuous network under the action of the nano silver wires. At the same time, when the pores are filled, better rebound performance can be achieved.
[0155] The highly conductive foam prepared in Examples 1 to 5 and the conductive foam in Comparative Examples 1 to 4 were cut into small squares of 5 mm × 5 mm × 2.5 mm (i.e., 5 mm in length, 5 mm in width, and 2.5 mm in height), and resistance and resilience tests were performed; specifically, the resistance value can be measured using a multimeter, and the resilience test can be performed by pressing the conductive foam to deform by 50%; after the resistance test, ultrasound was performed for 1 hour (ultrasonic power was 120 W), and then the resistance test was performed. The test results are shown in Table 1 below.
[0156] Table 1 - Performance test results of conductive foam in Examples 1 to 5 and Comparative Examples 1 to 4
[0157] Example Resistance (mΩ) <![CDATA[Rebound resilience (N / cm 2 )]]> Resistance after ultrasound (mΩ) Example 1 30 18 30 Example 2 28 18 28 Example 3 22 16 22 Example 4 15 23 15 Example 5 32 18 32 Comparative Example 1 1000000+ 2 1000000+ Comparative Example 2 210 3 5000 Comparative Example 3 1000000+ 1 1000000+ Comparative Example 4 550 2 1600
[0158] As shown in Table 1, in Examples 1 to 5, by cleaning the foam surface, growing nano seeds, growing nano silver wires, cleaning impurities, and heating and fusing, the resistance of the foam is low, which greatly improves the conductive performance of the foam, so that it can be used in the field of high conductivity. At the same time, since the nano silver wires inside the foam are more fully filled, the resilience of the foam is also greatly improved; and the resistance of the conductive foam remains unchanged after ultrasound, which shows that the silver nanowires have good adhesion inside the foam and will not fall off. In Comparative Example 1, the conventional nickel-plated conductive foam sold on the market only conducts electricity on the surface of the foam, and there is no filling of the holes inside the foam, so the resistance and resilience are much lower than those of the conductive foam in Examples 1 to 5.
[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly conductive foam, characterized in that: The following steps are involved: Soaking the foam in a silane coupling agent solution, and then washing the foam; The washed foam is immersed in a solution containing chloride ions and / or bromide ions, and then a silver salt is added and stirred to form nano seeds on the surface and inside of the foam; placing the foam with the nano seeds formed thereon in a first silver salt solution and heating it to form silver nanowires on the surface and inside of the foam; washing the foam formed with the silver nanowires; Curing the washed foam at 40-180°C; Wherein, the first silver salt solution comprises silver salt, ethylene glycol and polyvinyl pyrrolidone.
2. The method for preparing the highly conductive foam according to claim 1, characterized in that: The foam with the nano seeds is placed in the first silver salt solution, heated and stirred at 100-190° C., and the second silver salt solution is added dropwise to the first silver salt solution again; the reaction is stirred for 30-60 minutes; The second silver salt solution includes silver salt, ethylene glycol and polyvinyl pyrrolidone.
3. The method for preparing the highly conductive foam according to claim 2, characterized in that: The mass fraction of silver salt in the first silver salt solution is 0.5-10%, and the mass fraction of polyvinyl pyrrolidone is 0.5-10%; And / or, the mass fraction of silver salt in the second silver salt solution is 1-15%, and the mass fraction of polyvinyl pyrrolidone is 0.05-2.5%; and / or, the mass of the second silver salt solution is 20 to 150% of the mass of the first silver salt solution; And / or, the silver salt in the first silver salt solution and the silver salt in the second silver salt solution include at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide and silver acetate.
4. The method for preparing the highly conductive foam according to claim 1, characterized in that: The solution containing chloride ions and / or bromide ions comprises a chloride salt and / or a bromide salt and a first solvent; The chloride salt includes at least one of sodium chloride, potassium chloride, ferric chloride, ferrous chloride, cobalt chloride, nickel chloride, cupric chloride and zinc chloride; And / or, the bromide salt includes at least one of sodium bromide, potassium bromide, ferric bromide, ferrous bromide, cobalt bromide, nickel bromide, copper bromide and zinc bromide; and / or, the first solvent comprises at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol; And / or, the mass concentration of chloride salt or bromide salt in the solution containing chloride ions and / or bromide ions is 0.1-5%.
5. The method for preparing the highly conductive foam according to claim 1, characterized in that: The silane coupling agent solution comprises a silane coupling agent and a second solvent; The silane coupling agent includes at least one of KH-171, KH-172, KH-350, KH-360, KH-370, KH-550, KH-560, KH-570, KH-580, and KH-590; and / or, the second solvent comprises water and / or alcohol, and the alcohol comprises at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; And / or, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.01-5%.
6. The method for preparing the highly conductive foam according to claim 1, characterized in that: washing the foam formed with the silver nanowires with a third solvent; The third solvent comprises at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, ethyl acetate, butyl acetate, acetone, butanone, and methyl ethyl ether; And / or, the washing time is 5 to 60 minutes.
7. The method for preparing the highly conductive foam according to claim 1, characterized in that: The foam is immersed in a silane coupling agent solution and stirred at 100-1000 rpm for 10-120 minutes, and then washed with an alcohol solvent; the alcohol solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.
8. The method for preparing the highly conductive foam according to any one of claims 1 to 7, characterized in that: The washed foam is immersed in a solution containing chloride ions and / or bromide ions, stirred for 10 to 30 minutes, then a silver salt is added, and stirred again for 10 to 30 minutes to form nano seeds on the surface and inside of the foam; The silver salt is added in the form of a third silver salt solution, the third silver salt solution comprises a silver salt and a fourth solvent, and the silver salt comprises at least one of silver nitrate, silver chloride, silver iodide, silver sulfate, silver lactate, silver bromide, and silver acetate; The fourth solvent includes at least one of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, and glycerol; The mass concentration of silver salt in the third silver salt solution is 0.1-5%.
9. The method for preparing a highly conductive foam as claimed in claim 4, characterized in that: The second solvent includes water and alcohol, and the volume ratio of water to alcohol is 1:(1-3); And / or, the foam is polyurethane foam.
10. A highly conductive foam, characterized in that: The preparation method is as described in any one of claims 1 to 9.